Chikungunya: Transmisi dan Permasalahannya - Amirullah Amirullah; Endang Puji Astuti (Loka Litbang Kesehatan Pangandaran, 2011)
Abstract. One of the vector-borne diseases that outbreaks in the community is chikungunyafever, which the carrier is the mosquito vectors derived from the genus Aedes aegypti andAedes albopictus. The disease is not dangerous than malaria or dengue fever that can leadto death, chikungunya virus is self limiting disease. Losses resulting from this disease is thedecline in labor productivity due to loss of opportunity because the symptoms it causes. Thisreview describes the epidemiology of chikungunya virus and problem in public health